2020
DOI: 10.1186/s12913-020-05964-2
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported symptoms of depression and anxiety among informal caregivers of persons with dementia: a cross-sectional comparative study between Sweden and Italy

Abstract: Background Around 50 million people worldwide are diagnosed with dementia and this number is due to triple by 2050. The majority of persons with dementia receive care and support from their family, friends or neighbours, who are generally known as informal caregivers. These might experience symptoms of depression and anxiety as a consequence of caregiving activities. Due to the different welfare system across European countries, this study aimed to investigate factors associated with self-repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
12
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 51 publications
2
12
0
4
Order By: Relevance
“…In both countries, most of the caregivers who participated in the study were females, which is consistent with the results of previous works25–28 and with the central role played by females in the provision of informal care 2–4. In coherence with previous literature,39 41–48 the majority of Italian participants in our study provided care to a parent (in law) and spent more than 40 weekly hours of care, compared with their Swedish counterparts who provided care to spouse/partner and spent less than 10 hours per week providing care. Previous research showed that care for someone in one’s own household is more common in Southern European countries than in Northern countries.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In both countries, most of the caregivers who participated in the study were females, which is consistent with the results of previous works25–28 and with the central role played by females in the provision of informal care 2–4. In coherence with previous literature,39 41–48 the majority of Italian participants in our study provided care to a parent (in law) and spent more than 40 weekly hours of care, compared with their Swedish counterparts who provided care to spouse/partner and spent less than 10 hours per week providing care. Previous research showed that care for someone in one’s own household is more common in Southern European countries than in Northern countries.…”
Section: Discussionsupporting
confidence: 91%
“…This may be related to the lower median age of the Italian sample compared with the Swedish one. Caregivers from Southern European countries with a family-based care system often lack support in terms of formal services and professional training from the government 41–48. This shortcoming of support may increase their need for information and services.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the QoL of the informal caregivers included in our study, the results of EQ-5D-3L and EQ-VAS were illustrative of a very compromised QoL, where two or three domains of the EQ-5D-3L were affected (mainly the ability to perform usual activities, pain/discomfort, and anxiety/depression). In fact, previous studies reported depression symptoms among dementia informal caregivers (D'Aoust et al, 2015; Karg et al, 2018;Wulff et al, 2020). The domains of ability to perform usual activities and pain/discomfort were also the mostly affected in a recent Spanish study involving informal caregivers of PwD, however the values obtained for the means of EQ-5D-3L and EQ-VAS were extremely higher than the values obtained in our study (0.76 ± 0.22 mean for the EQ-5D-3L index score and 66 ± 13 mean EQ-VAS, comparing to 0.37 ± 0.28 and 60.7 ± 19.7, respectively, in our study) (Madruga et al, 2020).…”
Section: Discussionmentioning
confidence: 98%
“…Cultural and social factors are related to self-reported symptoms of anxiety and depression among informal caregivers. 40 We can speculate that differential emphasis on spiritual and existential elements, patient impairment (e.g., functional and behavioural) and the national health services arrangements are culturally-specific explanatory variables, however further studies are required to explore these.…”
Section: Discussionmentioning
confidence: 99%